2014
DOI: 10.1111/cea.12349
|View full text |Cite
|
Sign up to set email alerts
|

Siblings, asthma, rhinoconjunctivitis and eczema: a worldwide perspective from the International Study of Asthma and Allergies in Childhood

Abstract: BackgroundAssociations of larger families with lower prevalences of hay fever, eczema and objective markers of allergic sensitization have been found fairly consistently in affluent countries, but little is known about these relationships in less affluent countries.MethodsQuestionnaire data for 210 200 children aged 6–7 years from 31 countries, and 337 226 children aged 13–14 years from 52 countries, were collected by Phase Three of the International Study of Asthma and Allergies in Childhood (ISAAC). Associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
4
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(84 citation statements)
references
References 37 publications
7
67
4
6
Order By: Relevance
“…A recent large cohort study reported an inverse trend for the presence of allergic disease (such as hay fever/eczema) with an increasing number of total siblings, specifically older siblings [12] . These findings lend support to the hygiene hypothesis as an explanation for the increased incidence of allergic diseases [13] .…”
Section: Influence Of Birth Order On Allergic Sensitizationmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent large cohort study reported an inverse trend for the presence of allergic disease (such as hay fever/eczema) with an increasing number of total siblings, specifically older siblings [12] . These findings lend support to the hygiene hypothesis as an explanation for the increased incidence of allergic diseases [13] .…”
Section: Influence Of Birth Order On Allergic Sensitizationmentioning
confidence: 99%
“…The hygiene hypothesis posits that the rising prevalence of allergic disease is due to a reduction in exposure to infectious agents in modern industrialized society [12,13] . In our study, not being firstborn, exposure to passive smoking, keeping pets and living near busy roads were factors related to decreased AORs of allergic sensitization.…”
Section: Hygiene Hypothesismentioning
confidence: 99%
“…Penelitian oleh Ball 16 pada anak menunjukkan bahwa kehadiran >1 orang saudara kandung di rumah melindungi terjadinya asma. Hasil penelitian phase three of the international study of asthma and allergic in childhood (ISAAC) 17 pada anak usia 6-7 tahun dan usia 13-14 tahun menunjukkan bahwa memiliki >3 orang saudara menurunkan risiko rhinitis alergi (usia 6-7 tahun) dan asma (usia 13-14 tahun) dibandingkan anak tunggal. European community respiratory health study II (ECRHS II) melaporkan insidensi rhinitis alergi menurun dengan bertambahnya jumlah saudara kandung.…”
Section: Pembahasanunclassified
“…The number of siblings has been shown to be an important factor influencing the occurrence of allergic disease 17 and we chose therefore to investigate its relation with an objective marker of allergy i.e. skin prick test positivity.…”
Section: Examples Of Analyses On the Phase Two Datamentioning
confidence: 99%